Environmental Informatics and Soft Computing Paradigm: Processing of Cocos Nucifera Shell Derived Activated Carbon for Treatment of Distillery Spent Wash—A Solution to Environmental Issue. (11th November 2014) - Raut, N. B.; Saini, Dinesh Kumar; Shinde, G. B.
Abstract : Soft computing techniques are very much needed to design the environmental related systems these days. Soft computing (SC) is a set of computational methods that attempt to determine satisfactory approximate solutions to find a model for real-world problems. Techniques such as artificial neural networks, fuzzy logic, and genetic algorithms can be used in solving complex environmental problems. Self-organizing feature map (SOFM) model is proposed in monitoring and collecting of the data that are real time and static datasets acquired through pollution monitoring sensors and stations in the distilleries. In the environmental monitoring systems the ultimate requirement is to establish controls for the sensor based data acquisition systems and needs interactive and dynamic reporting services. SOFM techniques are used for data analysis and processing. The processed data is used for control system which even feeds to the treatment systems. Cocos nucifera activated carbon commonly known as coconut shell activated carbon (CSC) was utilized for the treatment of distillery spent wash. Batch and column studies were done to investigate the kinetics and effect of operating parameter on the rate of adsorption. Since the quantum of spent water generated from the sugar industry allied distillery units is huge, this low cost adsorbent is found to be an attractive economic option. Equilibrium adsorption date was generated to plot Langmuir and Tempkin adsorption isotherm. The investigation reveals that though with lower adsorption capacities CSC seems to be technically feasible solution for treating sugar distillery spent. Efforts are made in this paper to build informatics for derived activated carbon for solving the problem of treatment of distillery spent wash. Capsule . Coconut shell derived activated carbon was synthesized, characterized, and successfully employed as a low cost adsorbent for treatment of distillery spent wash.